Analýza nástrojů pro zobrazování struktury proteinů - Klemšová, Jarmila (Vysoké učení technické v Brně. Fakulta informačních technologií)
Tato práce se zabývá analýzou nástrojů pro prohlížení struktury proteinů. Pojednává o struktuře proteinů, databázích stuktur proteinů a formátu dat v nich uložených. Dále popisuje vybrané prohlížecí nástroje a skripty pro ně vytvořené. Součástí je i ukázková vizualizace.

In this thesis we analyze several tools for protein structure visualisation. We describe the structure of the proteins, the databases for storing protein structures and their data formats. Next part of the thesis, provides detailed information about selected visualisation tools and some scripts for them. The thesis also include an example of visualisation of the selected protein.
Analysis of Protein Structure Visualisation Tools
Keywords: databáze; pdb; proteiny; prohlížecí nástroje; vizualizace; database; pdb; proteins; visualisation tools; visualisation